Komunikasi Interpersonal Orang Tua Dalam Pembinaan Perilaku Anak Di Kelurahan Klaru Distrik Mariat Kabupaten Sorong - Nasution, Aida Aqsanti; Ahdiyanti, Istika (Al-Hikmah: Jurnal Dakwah dan Komunikasi, 2022)
The Hadrah Kuntulan Banyuwangi Tradition at the Inauguration of the Ikawangi Management in Sorong Regency. The type of research used is descriptive qualitative research using a da'wah approach, a cultural sociology approach. The data sources used are primary data sources and secondary data sources. The results of this study can be concluded that Hadrah Kuntulan has now been developed and preserved by native Banyuwangi residents in Sorong City. The inauguration of the Ikawangi Management in Sorong City often uses Hadrah as a procession ritual and as a form of gratitude to Allah SWT. The hadrah kuntulan tradition at the inauguration of the Ikawangi board is a hereditary tradition. Hadrah egrets are a form of gratitude to Allah SWT. Because this philosophy is taken from cranes, Javanese people say that egrets, when they get egret food, call their friends to share what they get. In this tradition, the implementation process begins when the musicians line up and play their instruments with a fast and firm rhythm. Then six teenage female dancers appeared, walking in a standing position. The hadrah kuntul tradition can be said to be 'Urf fluent, because within the purpose of hadrah kuntul there is one goal. More precisely, the hadrah kuntul tradition can be said to be 'Urf Sahih because within the purpose of the hadrah kuntul there is a good direction, that is, every movement contains meaning as a form of gratitude.